1996
DOI: 10.3354/dao024121
|View full text |Cite
|
Sign up to set email alerts
|

Use of random DNA amplification to generate specific molecular probes for hybridization tests and PCR-based diagnosis of Yersinia ruckeri

Abstract: Use of random DNA amplification to generate specific molecular probes for hybridization tests and PCR-based diagnosis of Yersinia ruckeri ABSTRACT We have developed a fast and convenient detection method for the etiological agent of enteric redmouth disease in rainbow trout, the bacterium Yersinia ruckeri, using the random amplification of polymorphic DNA (RAPD) technique to design specific primers for a polymerase chain reaction (PCR)-based diagnosis. In the RAPD genomic fingerprint of Y ruckeri, a specific b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Consequently, qPCR has been applied to the diagnosis of a wide range of pathogens from various sources including food products (Postollec, Falentin, Pavan, Combrisson & Sohier, 2011), faecal and environmental samples (B elanger, Boissinot, Clairoux, Picard & Bergeron, 2003;Rinttil€ a, Kassinen, Malinen, Krogius & Palva, 2004), and infected plant and animal tissues (Marancik & Wiens, 2013;Osman & Rowhani, 2006). These applications include assays for detection of Y. ruckeri (Argenton et al, 1996;Bastardo, Ravelo & Romalde, 2012), although commercial applicability of these particular methods and their value as a screening tool are limited, as they involve invasive or destructive sampling of putatively infected fish.…”
mentioning
confidence: 99%
“…Consequently, qPCR has been applied to the diagnosis of a wide range of pathogens from various sources including food products (Postollec, Falentin, Pavan, Combrisson & Sohier, 2011), faecal and environmental samples (B elanger, Boissinot, Clairoux, Picard & Bergeron, 2003;Rinttil€ a, Kassinen, Malinen, Krogius & Palva, 2004), and infected plant and animal tissues (Marancik & Wiens, 2013;Osman & Rowhani, 2006). These applications include assays for detection of Y. ruckeri (Argenton et al, 1996;Bastardo, Ravelo & Romalde, 2012), although commercial applicability of these particular methods and their value as a screening tool are limited, as they involve invasive or destructive sampling of putatively infected fish.…”
mentioning
confidence: 99%
“…Although we did not determine the detection limit with PCR, this method was more sensitive than plate culture; more infected fish were identified with the PCR method than by plate culture. Gibello et al (1999) also found rainbow trout that tested positive for Y. ruckeri by PCR but were negative based on the absence of bacterial growth on TSA and MacConkey agar plates; however, Y. ruckeri was isolated on TSA after tissue from these fish was cultured in enrichment broth for 48 h. A previously published PCR method did not detect Yersinia ruckeri in the blood of rainbow trout (Argenton et al 1996). Similar problems detecting other pathogens in blood have been attributed to PCR inhibitors (Iralu et al 1993, Klein et al 1997).…”
Section: Discussionmentioning
confidence: 99%
“…The greater speed and sensitivity of PCR compared to bacteriological culture of Yersinia ruckeri were discussed by Argenton et al (1996) and Gibello et al (1999). The use of blood for PCR does not require necropsy, and for experimental study of pathogenesis would allow repeated sampling of individual fish.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations